SoTL: A mechanism for understanding and finding solutions to teaching and learning challenges - Jo-Anne Vorster (University of Johannesburg, 2020)
The paper argues that the Scholarship of Teaching and Learning (SoTL) is a necessary strategy for mitigating the many teaching and learning challenges in South African higher education that prevent a large proportion of students from achieving academic success. Research suggests that well-structured and coordinated educational practices that are valued and supported by institutions are crucial for student success. While there exists a very useful body of scholarship on teaching and learning in higher education in South Africa, the persistently high levels of student failure and dropout across the system points to the need for more research into teaching and learning dilemmas in diverse institutional, disciplinary and classroom contexts. I argue that if more academics are to conduct SoTL, it has to be valued and supported by institutions and academic leaders. Even though more SoTL is needed to contribute to solving the many pedagogic dilemmas South African academics encounter, it is counter-productive to expect all academics to conduct SoTL. Rigorous SoTL requires immersion in educational ideas, concepts, theories and research processes. Many academics may not have the time or inclination to work in the area of SoTL, but I suggest that all must be scholarly teachers of their disciplines. Keywords: Scholarly teaching, Domains of SoTL, Collaborative SoTL Participatory parity, Curriculum How to cite this article: Vorster, J-A. 2020. SoTL: A mechanism for understanding and finding solutions to teaching and learning challenges. Scholarship of Teaching and Learning in the South. 4(2): 6-21. https://doi.org/10.36615/sotls.v4i2.149. This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/